Kesesuaian Kurikulum SMK Pertanian Berbasis Kebutuhan Dunia Kerja (Fokus: Kommpetensi Keahlian Agrobisnis Pengolahan Hasil Pertanian) - Subijanto, Subijanto; Sumantri, Darmawan (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
This study aimed to identify the link and match between the skills and competency of the Agricultural Vocational Secondary School graduates from the Agribusiness of Agricultural Product Processing Competency Skill and the competencies that the industry needs, and identify the mechanism in ensuring the link and match of the Agricultural Vocational Secondary School curriculum of the specific competency. The data was collected through a focus group discussion. The study results showed that the Agricultural Vocational Secondary School Curriculum has linked and matched with the competencies that the industry needs, referring to the certification for level two of the Indonesian National Qualification Framework. There was no formal steps and mechanism to link and match the curriculum of Agricultural Vocational Secondary School in the Competency Skill for Agribusiness of Agricultural Product Processing with the competencies that the industry needs. This study concluded that the curriculum of the Agricultural Secondary Vocational School focuses on The Competency Skill for Agribusiness of Agricultural Product Processing has linked and matched with the Certification Schema for Level Two of the Indonesian National Qualification Framework, set by the National Board for Professional Certification and the Directorate General for Primary and Secondary Education.